Comparative effectiveness of plant-derived compounds in keloid management: a review - Prananda, Arya Tjipta; Nugraha, Sony Eka; Situmorang, Putri Cahaya; Syahputra, Rony Abdi (Frontiers in Pharmacology, 2025)
Keloids are a challenging dermatological condition characterized by excessive scar formation beyond the original wound site, high recurrence rates, and limited treatment efficacy. Current therapies, such as corticosteroids, surgery, and radiotherapy, often yield suboptimal outcomes and adverse effects. This review evaluates the potential of plant-derived metabolites as safer and more effective alternatives for keloid management. Preclinical and clinical studies demonstrate that compounds like curcumin, epigallocatechin gallate (EGCG), and asiaticoside exhibit anti-fibrotic, anti-inflammatory, and antioxidant properties by modulating key pathways (e.g., TGF-β/Smad, NF-κB, and oxidative stress). Espite promising preclinical and early clinical findings, critical challenges hinder the clinical translation of these metabolites. These include poor and variable bioavailability, inconsistencies in extract standardization, and a paucity of large-scale, rigorously designed trials. Moreover, some metabolites may yield conflicting results or exhibit off-target effects in in vitro systems, necessitating caution in interpreting their true therapeutic potential. Future research should focus on optimizing drug delivery systems, conducting large-scale trials, and integrating personalized medicine approaches. Plant-derived metabolites represent a multi-targeted therapeutic strategy with the potential to address unmet needs in keloid treatment.